2004
DOI: 10.1557/jmr.2004.0261
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of white electroluminescent devices fabricated using conjugated polymer blends

Abstract: We report the characterization of white light emitting devices fabricated using conjugated polymer blends. Blue emissive poly[9,9-bis(4Ј-n-octyloxyphenyl)fluorene-2, 7-diyl-co-10-(2Ј-ethylhexyl)phenothiazine-3,7-diyl] [poly(BOPF-co-PTZ)] and red emissive poly(2-(2Ј-ethylhexyloxy)-5-methoxy-1,4-phenylenevinylene) (MEH-PPV) were used in the blends. The inefficient energy transfer between these blue and red light emitting polymers (previously deduced from the photoluminscence (PL) spectra of the blend films) enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 25 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Conjugated polymers have received a great deal of interest for a variety of applications, especially in displays; however, the production of white light has been problematic because the width of an emission peak from a single polymer species is generally not broad enough to cover the entire spectrum of visible light. White polymer light-emitting diodes (PLEDs) were prepared by introducing small amounts of red and green-emissive moieties grafted onto, , or doped into, a blue-emitting polymer. Energy transfer from the wide-gap host polymer to the smaller-gap species, followed by concurrent emission from the three chromophores, yields white light.…”
mentioning
confidence: 99%
“…Conjugated polymers have received a great deal of interest for a variety of applications, especially in displays; however, the production of white light has been problematic because the width of an emission peak from a single polymer species is generally not broad enough to cover the entire spectrum of visible light. White polymer light-emitting diodes (PLEDs) were prepared by introducing small amounts of red and green-emissive moieties grafted onto, , or doped into, a blue-emitting polymer. Energy transfer from the wide-gap host polymer to the smaller-gap species, followed by concurrent emission from the three chromophores, yields white light.…”
mentioning
confidence: 99%
“…Poly(91FV-co-9PV) [10] and MEH-PPV [9] were synthesized according to procedures outlined in the literatures. The properties of the polymers used in the blends are summarized in Table 1.…”
Section: Synthesis Of Poly(91fv-co-9pv) and Meh-ppvmentioning
confidence: 99%
“…In both vacuum-deposited small molecule devices and solution-processed polymer devices, control of the energy transfer between the red, green, and blue dyes is essential, and usually requires the introduction of very low levels of doping controls. Recently, we found that there is inefficient energy transfer between poly(fluorene) (PF) and poly (1,4- [7][8][9]. Therefore, it is possible to obtain white light emission from a blend of PF and PPV derivatives by controlling the blend ratio.…”
Section: Introductionmentioning
confidence: 99%
“…There are two major ways to get a white light emission from WPLEDs. The first is to blend red and blue polymer dyes together to form a single film . However, these devices usually face the difficulties of low efficiency and/or color instability due to intrinsic phase separation.…”
Section: Introductionmentioning
confidence: 99%